Self-similar rupture of viscous thin films in the strong-slip regime - Peschka, D; Muench, A; Niethammer, B (2010)
We consider rupture of thin viscous films in the strong-slip regime with small Reynolds numbers. Numerical simulations indicate that near the rupture point viscosity and van der Waals forces are dominant and that there are self-similar solutions of the second kind. For a corresponding simplified model the self-similar behaviour is analysed rigorously. There exists a continuous one-parameter family of exact self-similar solutions. In a certain parameter regime necessary and sufficient conditions for convergence to a self-similar solution are established. A conjecture on the domains of attraction of all self-similar solutions is presented and supported by numerical simulations. © 2010 IOP Publishing Ltd and London Mathematical Society.